Father’s knowledge and attitude towards breast feeding - Abhinaya, Abhinaya; T.S, Arunprasath; Padmasani, L.N (International Journal of Medical Research and Review, 2016)
Introduction: A father’s knowledge and attitude towards breastfeeding are very important for the success of breastfeeding practices. There is no uniform practice of including them in the education sessions in our country. Objectives: To assess the knowledge and attitude towards breastfeeding among fathers of infants aged 6 months to 2 years attending well baby clinic. Material and Method: A cross sectional study with convenient sampling was conducted on 93 fathers. A self-administered, pretested and pre-validated questionnaire with regards to breastfeeding practices was then distributed among the fathers. Results: 93 respondents completed this study. 70 fathers (75.3%) had babies exclusively breast fed between 4-6 months of age. 54 fathers (58.1%) had knowledge about breastfeeding before baby’s birth and 68(73.1%) were keen to get more information after baby’s birth. 90 fathers (96.8%) felt that they got required information , but only 34 (36.6.%) had received education from health care providers. Knowledge regarding exclusive breastfeeding (n=84), breast milk superiority,(n=86), emotional bonding created by breastfeeding (n=70) was adequate in most. Father’s age, education status, occupation, family type had no influence on knowledge or attitude. Father’s whose child was born by caesarean section or had co morbidities in neonatal period had better knowledge and positive attitude. Fathers with better knowledge had positive attitude towards breastfeeding, but this had no influence on duration of exclusive breastfeeding. Conclusion: Father’s knowledge was positively affected by health care exposure and education. Fathers with good knowledge had positive attitude towards breast feeding. Hence they should be included in discussions regarding breastfeeding in antenatal counselling.